Story Telling: Writing the Body to Recall Life in Kanehara Hitomi’s Autofiction and Charlotte Roche’s Wrecked - Flora Roussel (European Journal of Life Writing, 2022)
In their way of living obsessions and traumas, the protagonists of Autofiction and Wrecked embody the conscious or unconscious search for a solution: Writing serves as the medium to tell a story as well as a means of re-entry into life. The fragmented narratives presented by Kanehara and Roche disrupt any linear storytelling as they reveal the protagonists’ painful memories. Placing the body at the centre of the analysis, the argumentation focuses on the sexual and textual aspects of the body. Aiming to demonstrate how the use of storytelling in Autofiction and Wrecked symbolises a recalling to life, this article first thematises the function of sexuality and secondly looks to the narrative itself. The body thus helps a process of healing.